2008
DOI: 10.1002/hep.22345
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia induces RNA oxidation in cultured astrocytes and brainin vivo

Abstract: Oxidative stress plays a major role in cerebral ammonia toxicity and the pathogenesis of hepatic encephalopathy (HE). As shown in this study, ammonia induces a rapid RNA oxidation in cultured rat astrocytes, vital mouse brain slices, and rat brain in vivo. Ammoniainduced RNA oxidation in cultured astrocytes is reversible and sensitive to MK-801, 1,2-Bis ( A mmonia toxicity to the brain plays a key role in the pathogenesis of hepatic encephalopathy (HE), which defines a reversible neuropsychiatric syndrome freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 39 publications
8
109
1
2
Order By: Relevance
“…Ammonia intoxication and HE were shown to trigger PTN nitration and RNA oxidation in the rat and human brain, respectively (10,17,21,29). Therefore, we analyzed whether these effects could also be observed in brain tissue from liver-specific GS KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia intoxication and HE were shown to trigger PTN nitration and RNA oxidation in the rat and human brain, respectively (10,17,21,29). Therefore, we analyzed whether these effects could also be observed in brain tissue from liver-specific GS KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Northwestern blot analysis was carried out as described in SI Materials and Methods and previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that ammonia applied to cultured astrocytes, at concentrations of 100 and 200 μM, does not induce oxidative stress, while concentrations of ammonia >500 μM result in ROS generation (Görg et al, 2008 andMehrotra andTrigun, 2012). In vivo, blood and brain ammonia levels are significantly lower in CLD rats than in ALF (<250 μM in CLD compared to >800 μM in ALF, ( Bosoi et al, 2012 andJiang et al, 2009c)); however, cerebral oxidative stress was observed only in ALF rats.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In line with this possibility, it has been demonstrated that RNA is a target for oxidation during acute HE (Görg et al, 2008). These authors observed that 7% of total RNA was oxidized in cultures of astrocytes Fig.…”
Section: Discussionmentioning
confidence: 67%
“…exposed to 1 mM ammonia, while 6% of total RNA was found oxidized in cerebral cortex of hyperammonemic rats (Görg et al, 2008). Oxidized mRNA has been related to abnormal protein level and function (Nunomura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%